Identifikasi Bangunan Kolonial pada Hunian di Kecamatan Banda Sakti Kota Lhokseumawe sebagai Aset Heritage - Armelia Dafrina; Muhammad Muhammad; Dela Andriani; Riza Fitri (Jurnal Serambi Engineering, 2022)
Lhokseumawe is one of the cities in Aceh Province that the Dutch had visited during the colonial period. One of the traces as historical evidence is the residence of the Dutch who are different from the dwellings of the local community. Colonial architecture is an architectural style that comes from a mixture of European architecture and through a process of adaptation to form Dutch architecture during the Indonesian period under Dutch rule. This colonial architecture adapted to the local environment and climate resulting in a suitable and comfortable building. The object of the research is a residential house in Banda Sakti District, Lhokseumawe City. In this area there are historical buildings identified as the Dutch Colonial Heritage Area. The purpose of the study was to identify the existence of a residential house in Banda Sakti District, Lhokseumawe City through the external form of residential housing (vertical and horizontal organization of space, roof model, door model, window model, ladder laying system, ornaments and orientation) related to the external form of the building. This research method is a qualitative method through direct observation at the research site and interviews with homeowners. This research is focused on facade elements or on the outer form of residential houses (vertical and horizontal organization of space, roof models, door models, window models) related to the external form of the building.